Harmonization of the Convention on the Rights of the Child and Islamic Law in Efforts to Protect Children's Rights in Medan City - Muazzul, Muazzul (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Children are an inseparable part of a nation's sustainability, and thus, their rights must be legally and morally guaranteed. This research aims to examine the forms and implementation of child rights protection in Medan City from the perspectives of Islamic Law and the Convention on the Rights of the Child (CRC). Islamic Law emphasizes child protection through the teachings of the Qur’an and Hadith, which highlight the responsibilities of parents, families, and society in fulfilling children's basic needs and rights. Meanwhile, the 1989 Convention on the Rights of the Child, ratified by Indonesia through Presidential Decree No. 36 of 1990, provides an international framework for ensuring comprehensive and non-discriminatory child rights. This research uses a normative legal method with legislative and conceptual approaches, supported by literature review. The findings reveal that both Islamic Law and the CRC share fundamental principles of child protection, such as the best interests of the child, the right to life and development, and protection from violence. In Medan City, child protection efforts still face challenges; however, integrative measures combining religious values and positive law have been implemented to support children's rights fulfillment. This study recommends strengthening collaboration among the government, religious leaders, and communities to establish a more effective and sustainable child protection system.